GURU DAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Ambrosius L Edu; Margareta Saiman; Ismail Nasar (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The problem in this study is learning motivation of the elementary students. This paper wants to explore the role of teachers in increasing students' learning motivation. To explore this theme, the method used was qualitative research with the type of literature study. The results showed that the learning motivation of students in elementary schools was not optimal. This can be seen from the low desire to learn, not diligent in learning, likes to skip school hours, and shows less interest during learning. This problem can not be separated from the performance of teachers who have been focused on teaching activities. The teacher's personal touch on the basic problem in learning, namely learning motivation, has not been a concern of the teacher. For this reason, teachers must increase their role not only as teachers, but also as companions and motivators for student learning. The teacher's role in increasing students' learning motivation is to clarify the goals to be achieved, create a pleasant atmosphere in learning, use a variety of methods in learning, give praise for each student's success, give awards, evaluate, and give rewards and punishments.